The Intangibles (un)equality between manufacturing and service enterprises - Zlatković Radaković, Matea (Industrija, 2024)
Even though intellectual capital is treated as key determinant of enterprises’ high-above performance and sustainable competitive advantage, there is lack of systematic approach to understanding whether crucial differences really exist in the intellectual capital of manufacturing and services enterprises. To fulfil this gap, this paper tries to address question on differences in intellectual capital overall and its each component between manufacturing and services enterprises. Performed analysis is based on empirical research data collected from … respondents representing managers in enterprises of Republic of Srpska, Bosnia and Herzegovina. In order to address the research questions, the statistical difference in means was tested for each intellectual capital component in terms of manufacturing and service enterprises. To test the mean differences between the two types of enterprises appropriate parametric and non-parametric independent sample tests are used. The obtained results demonstrate that service enterprises have higher human capital, relational and renewal capital than manufacturing enterprises. Structural capital has more emphasized role in manufacturing enterprises. As enterprises move towards a service orientation, they need to change their approach to intellectual capital stocks and management, and in this acknowledging the existence of differences between a manufacturing and service enterprises is the first step. Research findings shed a new light on the differences between these enterprises in terms of the possession and management of intellectual capital.